Determination of Origin of Commercial Flavored Rapeseed Oil by the Pattern of Volatile Compounds Obtained via GC–MS and Flash GC Electronic Nose. Issue 3 (16th January 2020) - Zhang, Youfeng; Wu, Gangcheng; Chang, Chang; Lv, Yating; Lai, Wanxian; Zhang, Hui; Wang, Xingguo; Jin, Qingzhe
Abstract: Flavored rapeseed oil (FRO) is a typical hot‐pressed oil and is widely consumed in China due to its strong characteristic flavor and intensive color. In this study, volatile profiles of 33 representative commercial rapeseed oils in China are characterized by gas chromatography‐mass spectrometry (GC‐MS) and flash gas chromatography (GC) electronic nose system. 51 volatile compounds are identified and the nitriles (methallyl cyanide and 5‐cyano‐1‐pentene), aldehydes (nonanal, 3‐furaldehyde, and 5‐methyl‐2‐furancarboxaldehyde), alcohols (1, 5‐hexadien‐3‐ol, 2‐furanmethanol, and phenylethyl alcohol), and pyrazines (2, 5‐dimethyl‐pyrazine and 2, 6‐dimethyl‐pyrazine) are the major volatile compounds in FROs. Glucosinolate degradation products account for the highest proportion of these volatiles, which are found to have a positive correlation with the erucic acid content ( R 2 = 0.796, p < 0.01). FRO from Sichuan province in the southwest of China can be characterized by the obvious distinctions in flash GC electronic nose combined with principal component analysis, which indicates that the flash GC electronic nose can be used as a promising method to identify the origins of FRO. Practical Applications : This work is helpful for expanding the knowledge of volatiles of commercial flavored rapeseed oil. The data can also serve as a basis for the quality assessment of hot‐pressed rapeseed oil. Meanwhile, the flash GC electronic nose combined with principal component analysis can be used as a promising method for the classification of flavor rapeseed oil production areas. Abstract : This work is helpful for expanding the knowledge of volatiles of commercial flavored rapeseed oil. The data can also serve as a basis for the quality assessment of hot‐pressed rapeseed oil. Meanwhile, the flash GC electronic nose combined with principal component analysis can be used as a promising method for the classification of flavor rapeseed oil production areas.